Distinguishing Features of Anti-β2 Glycoprotein I Antibodies between Patients with Leprosy and the Antiphospholipid Syndrome - Arvieux, J.; Renaudineau, Y.; Mane, I.; Perraut, R.; Krilis, S. A.; Youinou, P. (Thrombosis and Haemostasis, 2002)
Anticardiolipin (ACA), anti-β2 glycoprotein I (β2GPI), and antiprothrombin antibodies of IgG and IgM classes were quantitated by enzyme-linked immunosorbent assays in 176 untreated leprosy patients across the histopathological spectrum. Positivity rates ranged from 21% (IgG ACA) to 30% (IgM anti-prothrombin) versus 4% in healthy controls (p <10-2 to 10-3). Levels of IgM anti-β2GPI and IgG ACA were significantly higher in lepromatous leprosy and multibacillary patient subgroups. IgG3 was the most common subclass reactive to both β2GPI and prothrombin in selected high-titer leprosy sera, unlike antibodies from patients with the antiphospholipid syndrome (APS) largely restricted to IgG2. In leprosy patients, but not in the APS control group, there was no statistical correlation between ACA and anti-β2GPI antibody levels. Likewise, a large fraction of anti-β2GPI positive sera (36/45 and 28/44 for IgG and IgM, respectively) were unreactive in the standard ACA assay. Most assayed anti-β2GPI antibodies from leprosy patients showed (i) ability to recognize both human and bovine β2GPI immobilized on non-irradiated polystyrene plates, (ii) concentrationdependent inhibition of binding by cardiolipin, and (iii) relatively high avidity binding to fluid-phase β2GPI, thereby differing from those found in APS. Finally, the location of the major epitopic region on the β2GPI molecule targeted by autoantibodies was different in leprosy and APS, as assessed by direct binding to domain Iand V-deleted mutants and competition with the mouse monoclonal antibody 8C3, directed at domain I. Thus, leprosy-related antiphospholipid antibodies comprise persistent IgG and IgM anti-β2GPI that differ from APS-related ones with respect to IgG subclass, avidity and epitope specificity, possibly reflecting distinct pathophysiological significance.
Keywords: Antiphospholipid syndrome; leprosy; β2 glycoprotein I; prothrombin